KOMODIFIKASI RAMADAN & COVID-19 DALAM IKLAN TELKOMSEL EDISI “TERUS JALANKAN KEBAIKAN” - Bayujati Prakoso; Khairul Syafuddin (Cakrawala - Jurnal Humaniora, 2020)
Nowadays, advertising is not merely having urgency as a means of promotion of commodities, but it has become the commodity itself that is worth selling to get a lot of financial profit. The concentration of advertisers turns into a commodity that sells (commodification). Advertising is a strategic pillar to be utilized by producers, including for producers of telecommunications service providers, Telkomsel. This research aims to uncover the significance of the commodification of Ramadan & Covid-19 in "Terus Jalankan Kebaikan" edition of Telkomsel ads. In this research used a critical paradigm, qualitative approach, and the Semiotics method of Charles Sander Pierce. The object of this research is the "Terus Jalankan Kebaikan" edition of Telkomsel ads in one minute duration. The results showed Telkomsel's advertisement "Terus Jalankan Kebaikan" has carried out the commodification of Muslim activities during Ramadan and the condition of Covid-19. This is demonstrated by the visualization of sending gifts, maintaining the relationship with the video call quota, beneficial to learn to read Al-Qur’an, access a seven-minute lecture video as part of running Ngabuburit Ramadan with the quota of streaming, online shopping in Telkomsel to share to the people in need, and do donation activities using the donation Tukar POIN feature. Meanwhile, we saw in Telkomsel advertisement that with a stable and strong Internet network, the need to gather with family can run smoothly and can run common good activities. The human goodness and need activities for social interaction are important points that are packaged in the advertisement.